Analisis Metode Perhitungan Harga Pokok Produksi (HPP) Full Costing Peternakan Ayam Petelur dengan Kandang Sistem Rabbit Farm House : Studi Kasus di Peternakan Rajawali Rabbit Farm House Kabupaten Sumedang - Anisah Nur Fadhilah; Refa Eka Nasarida; Rula Nadzira; Siti Nurjamilah; Yati Nurhajati (Jurnal Ilmu Sosial dan Humaniora, 2026)
The growth of the broiler farming industry in Sumedang Regency has driven the adoption of the "Rabbit Farm House" housing system, which boosts productivity through automated environmental control. However, this system entails a more complex production cost structure than conventional housing, involving investment costs, electricity expenses, equipment maintenance, and asset depreciation. Consequently, there is a need for accurate calculation of the cost of goods produced (COGP) to serve as a basis for setting selling prices, controlling costs, and making business decisions. In practice, however, many farmers still employ rudimentary cost-recording methods, failing to fully account for all production cost components. This study aims to analyze the calculation of the cost of goods produced for broiler farms using the Rabbit Farm House system in Sumedang Regency, employing a cost accounting approach. A descriptive method with a qualitative approach was used. Data were gathered through observation, interviews, and documentation regarding production activities and cost recording at the broiler farms. The analysis involved identifying, categorizing, and calculating all production cost components—including raw materials, direct labor, and overhead—to derive a more accurate cost of goods produced. The findings are expected to provide insights into the actual production cost structure and serve as a basis for farmers to set appropriate selling prices, improve cost efficiency, and enhance financial management. Furthermore, this study is expected to serve as a reference for the development and implementation of cost accounting practices within the broiler farming sector.